Religiousity and Psychological Well-Being of the Parmalim Community - Nenny Ika Putri Simarmata; Ronald P Pasaribu; Joshua Sahat P Tambunan; Christofel Martua Aritonang (Psikostudia : Jurnal Psikologi, 2023)
Parmalim is a belief in the Mulajadi Debate of Na Bolon, and this doctrine has existed since ancient times. As adherents of religious beliefs, parmalim adherents often receive different treatment from the society.  The study aims to understand and describe the influence of religiousity on the psychological well-being of the Parmalin community in North Sumatra. This research uses quantitative research methods. Sampling techniques in this study are non-random sampling with purposive sampling techniques. The research sample consisted of 78 people from the Parmalim Community in North Sumatra who had adhered to the Parmalim belief system for at least 11 years. Data collection was directly to the participants at Parmalim’s place of worship in Medan, and by online. Data analysis using a double linear regression test with the help of SPSS for Windows 17 The method of data collection using a psychological scale is the scale of Religiousness and the psychological well-being scale.  The psychological scale used is the Religiosity scale and the Psychological Well-Being scale. In this study, religiosity was measured using The Centrality of Religiosity Scale-15 (CRS-15) while Psychological well-being used The Scales of Psychological Well-being. The results of this study found that there was a positive influence of religion on psychological well-being among Parmalim believers, the contribution is 25.9%. Religiosity in the Parmalim Community is in the high category (85.9%).  Psychological well-being in supporters of parmalim beliefs is mostly in the high category of 68%, where individuals with high psychological wellness are able to be warm in relationships with others, have empathy, have a purpose in life and understand the principle of giving and receiving in a relationship.Parmalim merupakan sebuah  aliran kepercayaan terhadap Debata Mulajadi Na Bolon dan ajaran ini sudah ada sejak dahulu kala. Sebagai penganut aliran kepercayaan, para penganut parmalim seringkali mendapatkan perlakuan yang berbeda dari lingkungan sekitarnya. Penelitian ini bertujuan untuk melihat pengaruh religiusitas terhadap Psychological Well-Being Komunitas Parmalin di Sumatera Utara. Penelitian ini menggunakan metode penelitian kuantitatif. Teknik pengambilan sampel dalam penelitian ini adalah non random sampling dengan teknik purposive sampling. Sampel penelitian terdiri dari 78 orang dari Komunitas Parmalim di Sumatera Utara yang telah menganut aliran kepercayaan Parmalim minimal 11 tahun.  Pengumpulan data dilakukan secara langsung di 2 rumah ibadat Parmalim di Medan dan melalui online. Analisis data menggunakan uji regresi linear berganda bantuan SPSS for Windows 17. Metode pengumpulan data menggunakan skala psikologi, Skala psikologi yang digunakan adalah skala Religiusitas dan skala Psychological Well-Being. Dalam penelitian ini Religiusitas diukur menggunakan The Centrality of Religiosity Scale-15 (CRS-15) sementara Psychological well-being menggunakan skala The Scales of Psychological Well-being. Hasil dari penelitian ini ditemukan bahwa ada pengaruh positif religiusitas terhadap psychological well -being pada penganut kepercayaan parmalim yaitu sebesar 25.9%. Religiusitas pada Komunitas Parmalim berada pada kategori tinggi (85.9 %). Psychological well-being pada penganut kepercayaan parmalim kebanyakan berada pada kategori tinggi yaitu 68%, dimana individu dengan psychological well-being tinggi mampu bersikap hangat dalam berhubungan dengan orang lain, memiliki empati, memiliki tujuan hidup dan memahami prinsip memberi dan menerima di dalam suatu hubungan.